Cooperation amplifiers or flame-war battlefields: A comparative case study of virtual communities - Srbljinović, Armano (Array, 2007)
Various settings in which human communication takes place influence its nature and content. Communication infrastructure may provide positive or negative incentives to offline and online cooperation in communities. This paper investigates how particular socio-technical features of virtual communities influence cooperation among their members. Several earlier proposed sets of design guidelines are reviewed and used as evaluation frameworks for assessing cooperation potential of virtual communities. Instances of constructive cooperation as well as those of destructive tendencies within virtual communities are brought in relation to the compliance to the guidelines. The study aims to provide preliminary insights into the ability of various proposed sets of design guidelines to indicate features of virtual communities which are particularly advantageous or disadvantageous to the development of viable cooperative online communities.